Evaluation of Wound Healing and Pain Perception After Frenectomy Using 810 Nm Diode Laser in A Young Patient: A Case Report (Razi Medical Journal, 2025)
To assess the pain perception, wound healing, and advantages of 810 nm diode laser in the treatment of pediatric patients with highly attached upper labial frenum.  A 16-year-old female patient was referred from a pedodontist for highly attached upper labial frenum removal. During examination, the distance between the upper two central incisor gingival margins and the upper labial frenum was less than 2 mm. The patient was advised of a frenectomy, which was done on Monday, 27.11.2023, using an 810 nm diode laser in contact and in continuous wave mode with an output power of 1 W and initiated 400 µm tip diameter. The total time of the procedure was 15 min, and the time of laser application was approximately 90 s. The patient was advised to avoid hot drinks and spicy foods on the day of the procedure, and paracetamol tablets were prescribed to the patient if needed. The patient was recalled after one week, two weeks, one month, and 4 months for follow-up.  Complete wound healing was within two weeks, and optimal healing was noted after three months. After 4 months of follow-up, there is no relapse with normal mucosa. As well as no pain (on the procedure day and days after), prescribed depending on the patient's own words and Wong-Backer faces pain rating scale (in which she chose the first expression in many sessions, which indicated that there is no pain), and therefore, no need for analgesics. An 810 nm diode laser is an effective tool for frenectomy, as it provides fast healing with no bleeding, no pain during or after the procedure, and without the need for dressing, antibiotics, or analgesics.
Keywords: Highly Attached Labial Frenum, Frenectomy, Diode Laser, 810 nm, Wound Healing, Pain Perception.